Numerical modeling of injection-induced earthquakes based on fully coupled thermo-poroelastic boundary element method. (November 2022) - Sabah, Mohammad; Ameri, Mohammad Javad; Hofmann, Hannes; Ebrahimi, Mohammad
Highlights: A fully-coupled Thermo-Hydro-Mechanical approach was developed to study injection-induced seismicity and permeability enhancement in low permeable reservoirs. Fracture deformation and transport processes were modeled using thermo-poroelastic displacement discontinuity method combined with Galerkin and Petrov Galerkin finite element methods. Constitutive behavior of fault friction was captured using rate-and-state friction model incorporating aging law for history of sliding. Traffic Light System-based injection protocols yield higher potential in enhancing the fault permeability. Volume-Controlled fluid injection are far more effective in reducing the seismic risk. Abstract: In recent years, there has been a substantial increase in the induced seismicity associated with geothermal systems. However, understanding and modeling of injection-induced seismicity have still remained as a challenge. This paper presents a two-dimensional fully thermo-hydro-mechanical (THM) coupled boundary element approach to characterize the fault response to forced fluid injection and assess the effect of different injection protocols on seismic risk mitigation as well as permeability enhancement. The laboratory-derived rate-and-state friction law was used to capture the frictional paradigm observed in mature faults produced in granite rocks. All phases of stick-slip cycles, including aseismic slip, propagation of dynamic rupture, and interseismic periods, were simulated. The modeling results showed that the residual values of effective normal stress and static shear stress after a particular event completely dominate the constitutive behavior of fault friction during the next seismic event. The seismic energy analyses indicated that there is a negative correlation between the seismic magnitude and the total injected volume, such that a prolonged monotonic injection eventually results in the steady slip, rather than the seismic slip. Several fluid injection protocols were designed based on a volume-controlled (VC) approach and traffic light systems (TLS) to explore their effectiveness on the seismic risk mitigation and permeability enhancement. The results showed that cyclic injection based on TLS is the most effective approach for irreversible permeability enhancement of faults through promoting slow and steady slips. Our numerical simulations also revealed that fluid extraction (backflow-fixing bottom hole pressure at atmospheric pressure), regardless of the injection style, can considerably reduce the seismicity-related risks by preventing the fast-accelerated fracture slip during the post-injection stage. This study presents novel insights into modeling the rate-and-state governed faults exposed to forced fluid injection, and provides useful approaches for shear stimulation of faults with reduced seismic risks.